2020
DOI: 10.1186/s40001-020-00420-7
|View full text |Cite
|
Sign up to set email alerts
|

The effects of aqueous extract of Maca on energy metabolism and immunoregulation

Abstract: Background: In the present work, we investigated the effects of aqueous extract of Maca (AEM) on energy metabolism and immunoregulation in spleen-deficient mice. Method: We established a cyclophosphamide-induced spleen-deficiency model with ginseng, a herb that strengthens splenic function, as a control. Sixty male Kunming mice were randomly divided among 5 groups: normal, model, ginseng control (1.5 g/kg), AEM high dose (1.5 g/kg), and AEM low dose (0.75 g/kg). All animals, except those in the normal group, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 20 publications
1
16
0
Order By: Relevance
“…The results of this study showed that the addition of maca promotes skeletal muscle hypertrophy and differentiation. Studies thus far have shown that maca promotes reproductive health, neuroprotection, antioxidants, antifatigue, antitumoral, liver protection, anti-memory impairment, and immune regulation [ 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 ]. The results of our study corroborate multiple antiaging effects of the natural food maca, which may be helpful to prevent sarcopenia and improve the quality of life of aging people.…”
Section: Discussionmentioning
confidence: 99%
“…The results of this study showed that the addition of maca promotes skeletal muscle hypertrophy and differentiation. Studies thus far have shown that maca promotes reproductive health, neuroprotection, antioxidants, antifatigue, antitumoral, liver protection, anti-memory impairment, and immune regulation [ 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 ]. The results of our study corroborate multiple antiaging effects of the natural food maca, which may be helpful to prevent sarcopenia and improve the quality of life of aging people.…”
Section: Discussionmentioning
confidence: 99%
“…16,31 Maca extracts or maca polysaccharides have been reported to activate parenteral immune cells in vivo, but the mechanism is still unclear. 24,32 The results in this study may provide a possible mechanism.…”
Section: Papermentioning
confidence: 69%
“…Resent study demonstrated that testosterone could prevent depression through MAPK/ERK2 signaling pathway ( 63 ). Linoleamide is an important active ingredient of Maca, which could regulate the energy metabolism and increased the antioxidant capacity ( 64 ).…”
Section: Discussionmentioning
confidence: 99%